Access to antiretroviral therapy among HIV/AIDS patients in Chiang Mai province, Thailand - Woraluck Himakalasa (2018)
The objective of this study is to investigate the access to antiretroviral treatment among human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) patients in Chiang Mai province, Thailand. Access to antiretroviral treatment is defined in terms of availability, affordability, and acceptability. The data for the study were collected during the period of April 1, 2012-May 31, 2012 from a sample of 380 HIV/AIDS patients in eight hospitals who had received antiretroviral treatment for more than 6 months at the time of data collection. The results of the study show that for most patients, the average traveling time to access health care was acceptable, but the nearly half day waiting time caused them to be absent from their work. In particular, it took longer for patients in the rural and lower income groups to access the treatment than the other groups. Their travel times and food costs relating to the treatment were found to be relatively high and therefore these patients had a higher tendency to borrow or seek financial assistance from their relatives. However, due to improvements in the access to treatment, most patients were satisfied with the services they received. The results imply that policy should be implemented to raise the potential of subdistrict hospitals where access to antiretroviral treatment is available, with participating HIV/AIDS patients acting as volunteers in providing services and other forms of health promotion to new patients. Privacy issues could be reduced if the antiretroviral treatment was isolated from other health services. Additionally, efforts to educate HIV/AIDS patients and society at large should be made. © 2013 Himakalasa et al.